Studi Teori Kritis dalam Hubungan Internasional - Rendi Prayuda, Rio Sundari, Fitrisia Munir (Journal of Diplomacy and International Studies, 2021)
International Relations, a branch of political science, is the study of foreign affairs and global issues among states in the international system, including the role of states, intergovernmental organizations, nongovernmental organizations, and multinational corporations. International Relations is a field of academia and public policy and can be positive or normative as it seeks to analyze and formulate the foreign policies of particular states. Theory provides a picture of how the world it seeks to influence works. It is difficult to make good policy if the basic organizing principles of our minds are wrong; likewise, it is very difficult to build theory without knowing much about the real world. Everyone uses theory and disagreements about policy are usually the result of disagreements about the factors that determine an international event or phenomenon.